Impact resistance cryogenic bunker fuel tanks: - Voormeeren, L.O.; Atli-Veltin, B.; Vredeveldt, A.W. (American Society of Mechanical Engineers (ASME), 2014)
The increasing use of liquefied natural gas (LNG) as bunker fuel in ships, calls for an elaborate study regarding the risks involved. One particular issue is the vulnerability of cryogenic LNG storage tanks with respect to impact loadings, such as ship collisions and dropped objects. This requires an understanding of the impact resistance of the storage tanks and the actual loads to be expected. No substantial literature exists on the actual energy absorbing capacity (crashworthiness) of cryogenic tanks. Main issues are material properties under cryogenic/moderate strain rate conditions and failure mechanisms associated with large deformation - fluid structure interaction, in particular the liquid-full condition. This paper reports material properties of stainless steel 304 at both ambient and cryogenic conditions. Also the effect of strain rate is addressed. Moreover, it describes and compares two approaches of predicting the effect of the 'liquid-full' condition on the impact resistance of LNG storage tanks. The first approach follows a multi-material Arbitrary-Lagrangian-Eulerian (ALE) formulation, whereas the second approach captures the fluid-structure interaction through an analytical loading subroutine, calculating the internal pressure as a function of tank volume decrease. Results of impact experiments on partially liquid-filled small-scale storage tanks are presented. The calculation methods have been validated against the experimental results. The results of the validation show that the crashworthiness of stainless steel (cryogenic) storage tanks can be well predicted through both the ALE and the analytical formulation.